(untitled) (Revista de História da UEG (REVHIST), 2024)
The objective of this paper is to point out some possible strategies for social mobility, especially advancement, used by women in the captaincy of Minas, during the 18th century, prioritizing the experience of enslaved and freed women. The topic of social mobility present in Portuguese America has already been extensively researched and offers us a wide range of studies that work with the ascension, inclusion and social exclusion of different groups that inhabited this space during the colonial period. We understand that social ascension was a constant search for these individuals, in order to maintain a better social position in this Old Regime society, in which status was fundamental. We will seek to demonstrate, based on studies dedicated to understanding different strategies for female social mobility, what options were available to this group. We will focus on understanding how these options worked, specifically for freed and enslaved women, since most women in the captaincy of Minas were in these positions.Keywords: Women. Social mobility. Minas Gerais. 18th century.